Provision of social services in EU countries Reform of the national framework for the provision of social services in Spain - Llena-Nozal, Ana (OECD Publishing, 2022)
This paper provides an overview of how social services are organised in European Union countries. With a special focus on Spain and countries with federal or semi-federal organisation, the paper starts by analysing social services from a legal perspective. It provides a comparative perspective on several concrete aspects of social services: sources of funding (national, regional, local, etc.), organization of service provision, expenditure, human resources, governance and coordination between institutions. The analysis finds that, despite differences across countries, there is no link between the existence of a comprehensive national social services laws and the comprehensiveness of the social service offer (the main differences concern family services and housing services in countries which consider housing as a right). There exist large differences in the contribution of central, regional, and local governments to social expenditure. Spending more on services does not necessarily imply spending less in cash transfers. Indeed, it appears that Nordic countries, that spend more on services as a share of their GDP, also spend more on cash transfers. Finally, the paper stresses the important role of the information technology and the horizontal and vertical coordination mechanisms to improve service quality and accessibility
Keywords: Social Issues/Migration/Health; Employment; Spain